Improved industrial induction time-based technique for evaluating kinetic hydrate inhibitors - Mohammad-Taheri, Mahboobeh; Tohidi, Bahman; Ghanbari, Bahram; Taheri Rizi, Zahra (Frontiers in Chemistry, 2024)
Kinetic hydrate inhibitor laboratory testing before field application is one of the key priorities in the oil and gas industry. The common induction-time-based technique is often used to evaluate and screen of kinetic hydrate inhibitors (KHIs). However, the main challenge relates to the stochastic nature of hydrate nucleation observed in fresh systems, which often results in scattered data on hydrate formation with unacceptable uncertainties.A much more precise KHI evaluation method, called the crystal growth inhibition (CGI) method, provides comprehensive insights into the inhibitory behavior of a kinetic hydrate inhibitor, including both hydrate formation and decomposition. Given that the industry does not require this much information, it is not feasible to invest both high time and cash in this strategy.This study aims to provide a cost-effective technique that presents maximum data accuracy and precision while spending relatively low resources of time and cost. In this regard, the impact of waterhydrate-memory on improving the accuracy and repeatability of the results of the induction-time-based technique, called the IT method, was examined.First, the concept of water-hydrate-memory, which contains information about how it is created, was reviewed, and then the factors influencing it were identified and investigated experimentally, like "heating rate of hydrate dissociation" and "water-hydrate-memory target temperature during heating".Finally, a procedure was developed based on the background information from the earlier sections to compare the consistency of the results, which originates from the conjunction of water-hydratememory with the induction time technique. Results of replications at KHI evaluation target temperature of 12.3-12.4 °C and 11.5-11.7 °C showed that more repeatable data was obtained by applying waterhydrate-memory and a more conclusive decision was made in evaluating KHI performance compared to an induction-time-based technique. It seems that combining the induction-time-based technique with water-hydrate memory introduced as the HME method, leads to more definitive evaluations of KHIs. This approach is expected to gain popularity soon, even surpassing the accurate but complex and time-consuming CGI method.